2022
DOI: 10.3389/fnins.2022.1056793
|View full text |Cite
|
Sign up to set email alerts
|

Masked face is looking at me: Face mask increases the feeling of being looked at during the COVID-19 pandemic

Abstract: BackgroundAs the COVID-19 global pandemic unfolded, governments recommended wearing face masks as a protective measure. Recent studies have found that a face mask influences perception; but how it affects social perception, especially the judgment of being looked at, is still unknown. This study investigated how wearing a mask influences the judgment of gaze direction by conducting a cone of direct gaze (CoDG) task.MethodsIn Experiment 1, three types of masked faces were considered to investigate whether the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
4
2
0
Order By: Relevance
“…The findings of our study showed that social attention orienting triggered by gaze can be modulated by face masks, which is in line with previous studies showing that face masks affect judgment of gaze directions 40 , 41 . One possible explanation for the reduction of GCE triggered by masked faces is that wearing masks is considered a pro-social behaviour while wearing no mask is considered antisocial behaviour.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of our study showed that social attention orienting triggered by gaze can be modulated by face masks, which is in line with previous studies showing that face masks affect judgment of gaze directions 40 , 41 . One possible explanation for the reduction of GCE triggered by masked faces is that wearing masks is considered a pro-social behaviour while wearing no mask is considered antisocial behaviour.…”
Section: Discussionsupporting
confidence: 93%
“…The current study provides new evidence that the perception processing of gaze direction can be modulated by face masks, which is in line with previous studies showing that face masks affect judgment of gaze directions 39,40 . However, the ndings of our study were not in line with the results of Dalmaso 22 , which showed that face masks did not alter the gaze-cueing effect.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that much like when eye-region cues are less reliable, a reduction in the reliability of lower face cues increases gaze direction uncertainty, thereby increasing the range of angles at which gaze is perceived as self-directed 10 12 . Two recent studies, published subsequent to completion of data collection for the present study, also reported an increase in the width of the CoDG when perceiving gaze in masked compared to unmasked faces 48 , 49 . While the width of the CoDG increased only slightly for masked faces in our study (0.3°), this is closely aligned with an increase of 0.28° reported by 48 .…”
Section: Discussionsupporting
confidence: 71%
“…an increase in the width of the CoDG). Indeed, two recent studies, published subsequent to completion of data collection for the present study, reported an increase in the width of the CoDG when perceiving gaze in masked compared to unmasked faces 48 , 49 . Additionally, the relative extent to which people weight eye-region and non-eye-region cues during gaze perception could affect the extent to which face masks impact their perception of gaze direction.…”
Section: Introductionmentioning
confidence: 96%